L’educazione alla differenza oggi. Formare l’altro - Dameri, Renzo (Studi sulla Formazione/Open Journal of Education, 2014)
Nowadays human relationships are dominated by a virtual interactivity based on nicknames or fakes which brings into question real trustworthiness and the ethical nature of sharing. Friendship, feelings and love are less intense, thoughts become fragmented like text messages and can be controlled by a simple “click”. As Levinas pointed out, relationships cannot be considered as a group of artificial or technological certainties anymore; they become open and real and they are based on the understanding of the Other. This Other, who pre-exists us, should be reconsidered in an appropriate way: we should start by considering his story, environment and habits, in order to truly understand him. Tolerance towards other people is not enough anymore; a tolerant person always tends to feel superior to those who are tolerated. Living together is possible only if we share with reciprocity.